Selected standards and policy statements of special interest to women workers adopted under the auspices of the ILO (ILO GenevaCH, 1980)
Contains selected provisions of international instruments and policy statements of special concern to women which have been adopted under the auspices of the ILO. These relate to human rights, employment, working conditions, social security, industrial relations, selected categories of workers, and labour administration.
Includes bibliographical references